ATTEMPTS TO SEARCH FOR AN ISLAMIC ECONOMIC DEVELOPMENT MODEL (ANALYSIS OF PHILOSOPHICAL THOUGHT MUSA ASY'ARIE) - MUHAMMAD KHAQIM; AGUS ARWANI (Universitas Islam Negeri Imam Bonjol Padang, 2019)
Reflection on Islamic thought is no longer concerned with the problem of indigenization of Islam which is more likely to conservation tradition, even leads to a syncretism that almost eliminates the orthodoxy of Islam. Musa Asy'arie is a postmodern intellectual Muslim figure in Indonesia who, with his philosophical ability, is anxious to give a strict critique as well as a clear direction to the economic development of Muslims so that the Islamic economy becomes an outlet for poverty and injustice to society. Type of methodology in this research is literature research with focus of study of Islamic economic thought Musa Asy'arie. This qualitative research is focused on a written document in the form of text produced by Musa Asy'arie. The approach used in this research is phenomenology approach. The phenomenological approach is intended to examine, to reveal the biography, his work and the pattern of his thought development from the perspective of history, that is, from the social and political conditions of the culture at that time. The research results of Musa Asy'arie' thoughts in Islamic economics refers to things that are of fundamental Islamic economic value which include the first divine principle which is where the deity or Gods, the second is the humanitarian province, the three are based on social concern or with other sentences more important piety social rather than individual piety.